1975
DOI: 10.1042/cs0490485
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Noradrenaline Excretion and Renal Function in Normal and Hypertensive 50-year-Old Men

Abstract: 1. Sympathetic nervous system activity, measured by urinary noradrenaline excretion, was determined in a group of untreated hypertensive subjects (n = 35), a reference group (n = 80) and a normotensive group (n = 51), all derived from a random population sample of 50-year-old men. It was compared with casual and resting blood pressure, urinary sodium excretion, urinary cretinine concentration and glomerular filtration rate. Hypertension was defined as systolic pressure greater than 175 or diastolic greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…However, if plasma noradrenaline is elevated in hypertension, an increase in urinary excretion of either free catecholamines or their principal metabolites would be expected. We have been unable to demonstrate such an increase and our findings are supported by similar recent data reported by Berglund, Tibblin & Aurell (1975).…”
Section: Discussionsupporting
confidence: 86%
“…However, if plasma noradrenaline is elevated in hypertension, an increase in urinary excretion of either free catecholamines or their principal metabolites would be expected. We have been unable to demonstrate such an increase and our findings are supported by similar recent data reported by Berglund, Tibblin & Aurell (1975).…”
Section: Discussionsupporting
confidence: 86%
“…In several more recent studies in which age was considered as a factor, circulating or urinary NE was found to be within the normal range in the large majority of patients with borderline or established essential hypertension [17,20,70,92,94,107,109,110,124,138,186,188] (Fig. 2).…”
Section: Essential Hypertensionmentioning
confidence: 92%
“…-Determination of plasma noradrenaline concentration [noradrenaline] is currently throught to be a useful index of Correspondence: Dr H. Ibsen, Department of Clinical Physiology, Glostrup Hospital, 2600 Glostrup, Denmark. sympathetic nerve activity (Christensen, 1979;Lake, Ziegler, Coleman & Kopin, 1977). Whereas some investigators have found increased plasma [noradrenalinel or increased urinary excretion rate for catecholamines (De Champlain, Farley, Cousineau & Van Ameringen, 1976;DeQuattro, Campese, Miura & Meijer, 1976;Esler, Julius, Zweifler, Randall, Harburg, Gardiner & DeQuatro, 1977) in a sizeable fraction of patients with essential hypertension, others have found completely normal values (Berglund,Tibblin & Aurell, 1975;Lake el al., 1977;Pedersen & Christensen, 1975).…”
Section: Introductionmentioning
confidence: 94%